Effect of Soft-Hard Segment Content on Properties of Palm Oil Polyol based Shape Memory Polyurethane - Darman, A; Ali, ES; Zubir, SA (AMER INST PHYSICS, 2024)
Shape memory polymers (SMP) are smart materials with the ability of changing shape when subjected to external stimuli. In this work, the shape memory polyurethane (SMPU) has been synthesized via two step bulk polymerization method by replacing up to 40% molar ratio of petroleum-based polyol using palm oil-based polyols (POP). This effort was done with the purpose of reducing the usage of petroleum-based polyol due to environmental awareness. The main objective is to investigate the effects of different polyol/isocyanate/1,4-butanediol molar ratio in relation to soft-hard segment content towards the mechanical and shape memory properties of the resulting SMPU. The mechanical properties were improved with POP addition and optimum performance of tensile properties were obtained within 35 to 40% of hard segment content. Tensile strength increased with increasing POP content but after 40% of hard segment content, the properties decreased. On the other hand, the modulus significantly reduced with an increase of hard segment content. Crystallinity also decreased with decreasing of polycaprolactone diol (PCL) content as more POP content was added. Shape memory properties of PU 165 is better than PU 154 in terms of the ability to return to its original shape since all of PU 165 samples showed 100% recovery. In general, the addition of palm oil-based polyol showed improvement in mechanical and shape memory properties as compared to pristine SMPU.